2021
DOI: 10.1021/acs.jmedchem.0c01786
|View full text |Cite
|
Sign up to set email alerts
|

U.S. FDA Approved Drugs from 2015–June 2020: A Perspective

Abstract: In the present work, we report compilation and analysis of 245 drugs, including small and macromolecules approved by the U.S. FDA from 2015 until June 2020. Nearly 29% of the drugs were approved for the treatment of various types of cancers. Other major therapeutic areas of focus were infectious diseases (14%); neurological conditions (12%); and genetic, metabolic, and cardiovascular disorders (7−8% each). Itemization of the approved drugs according to the year of approval, sponsor, target, chemical class, maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
267
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 465 publications
(269 citation statements)
references
References 197 publications
(357 reference statements)
0
267
1
1
Order By: Relevance
“… 20 While this could be somehow expected, 36 the extent of the use of fluorine might possibly surprise some. Indeed, a recent analysis made on FDA-approved drugs from 2015 to 2020 showed that 26% of drugs displayed fluorine, 37 already a very high number, but in our analysis we find 40% of drugs in the same time frame (compared to 17% in the first four years of the century) and 55% of fluorinated drugs issued a name in 2020.…”
Section: Analysis Of the Medicinal Chemistry Of The Inns In The Last 20 Yearscontrasting
confidence: 75%
“… 20 While this could be somehow expected, 36 the extent of the use of fluorine might possibly surprise some. Indeed, a recent analysis made on FDA-approved drugs from 2015 to 2020 showed that 26% of drugs displayed fluorine, 37 already a very high number, but in our analysis we find 40% of drugs in the same time frame (compared to 17% in the first four years of the century) and 55% of fluorinated drugs issued a name in 2020.…”
Section: Analysis Of the Medicinal Chemistry Of The Inns In The Last 20 Yearscontrasting
confidence: 75%
“…[24] We recently analysed that nitrogen heterocyclics still hold the major share of small molecules in the US FDA approved drugs, including pyrazole, indazole, pyridine, etc. [25] Elexacaftor, darolutamide, zanubrutinib, erdafitinib, voxelotor and entrectinib are the FDA approved pyrazole-based drugs for the treatment of various diseases, including cancer, also (Figure 1). [25,26] Thus, the pyrazole ring has attracted much attention for the synthesis due to its diverse biological properties and accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Elexacaftor, darolutamide, zanubrutinib, erdafitinib, voxelotor and entrectinib are the FDA approved pyrazole-based drugs for the treatment of various diseases, including cancer, also (Figure 1). [25,26] Thus, the pyrazole ring has attracted much attention for the synthesis due to its diverse biological properties and accessibility. [27] Teloxantrone and iosoxantrone are the important pyrazole-based topo II inhibitors that are under clinical trial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations